2013
DOI: 10.1002/bjs.9128
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis in abdominal aortic aneurysm

Abstract: These findings demonstrated lymphatic vessel involvement in end-stage AAA disease, which was associated with the degree of inflammation, and confirmed the involvement of neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…One important advantage of targeting angiogenesis is that rapid, persistent and specific targeting can be achieved with different probes, which endows an excellent efficiency and imaging contrast. The endothelial cells of newly formed vessels express high levels of CD105, also known as endoglin, on their surfaces (17). We have previously demonstrated the efficacy of a CD105 targeted antibody, TRC105, for in vivo imaging of angiogenesis (18–21).…”
Section: Introductionmentioning
confidence: 99%
“…One important advantage of targeting angiogenesis is that rapid, persistent and specific targeting can be achieved with different probes, which endows an excellent efficiency and imaging contrast. The endothelial cells of newly formed vessels express high levels of CD105, also known as endoglin, on their surfaces (17). We have previously demonstrated the efficacy of a CD105 targeted antibody, TRC105, for in vivo imaging of angiogenesis (18–21).…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal aortic aneurysm (AAA) is a progressive condition affecting mainly older men . Aneurysms typically grow by 2 mm per year and once the size exceeds 55 mm there is an increased risk of rupture, when patients are considered for open (OAR) or endovascular repair (EVAR) .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Scott et al [47] attempted to research the relationship between inflammation and neovascularization in AAA tissue. The results showed that the aneurysm wall contained high levels of inflammatory infiltrate, while microvascular densities of blood ( P < 0.001) and lymphatic ( P = 0.003) vessels were significantly increased in AAA samples compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…Vascularity as expressed by positive staining for CD31, CD105, and D2-40 correlated positively with inflammation, while increased VEGFR-3 and VEGF-A expression was observed within inflammatory areas of AAAs. These results suggest lymphatic vessel involvement in AAA disease, associated with the extent of inflammation [47]. …”
Section: Resultsmentioning
confidence: 99%